STUDI ALOMETRI DAN HUBUNGAN PANJANG BERAT IKAN TAWES (Barbonymus gonionotus) DI ALIRAN SUNGAI DEMPOK DESA GAMPINGAN KECAMATAN PAGAK KABUPATEN MALANG JAWA TIMUR - Ganjar Adhywirawan Sutarjo; Sony Andriyawan; Fazat Aiman (Universitas Sriwijaya, 2021)
Tawes (Barbonymus gonionotus) is one of the fish species whose habitats are in the Sengguru River, Gamping Village, Pagak District, Malang Regency, East Java. Research was conducted to see the growth and relationship of length and weight of tawes fish (Barbonymus gonionotus) for six months from February to July 2020. The data from the measurement of length and weight of each fish will be analyzed to determine the nature of its growth, whether allometric (b?3) or isometric (b=3). Negative allometric growth (b<3) is the increase in length faster than weight gain, while the weight gain is faster than the increase in length is a positive allometric growth (b>3), if the growth in length and weight is balanced it is called isometric (b=3). The results consisted of 240 Tawes (Barbonymus gonionotus), which had a length range of 145 to 285 mm and weights of 40,4 to 496,2. The length and weight relationship were then analyzed with the linear regression equation obtained the results in February W = 0,000926L2,206, March W = 0,012377L1,726, April W = 2,64E-06L3,308, May W = 0,000492L2,323, June W = 4,62E-05L2,781 dan July W = 7,76E-05L2,680. February, March, May, June and July showed negative allometric fish growth patterns, while in April showed positive allomertic growth patterns. Keywords: Barbonymus gonionotus, growth, long strenuous relationship